CHANGES IN COLOSTRUM COMPOSITION IN LACTATING INDIAN WOMEN HAVING MEDICAL COMPLICATIONS DURING PREGNANCY - DR M.PRASANTHI MD; DR K.AMBIKA DEVI MD; DR J.RAMA RAO MD (International Journal of Pharma and Bio Sciences, 2013)
Colostrum is specifically adapted to the needs of the newborn. Biochemical composition of colostrum makes it the best infant food during first 6 months of life .Colostrum provides all the essential components of nutrition and passive immunity required by the newborn.Complications during pregnancy such as pregnancy induced hypertension and anaemia are common among Indian women.The effect of these complications on composition of colostrum is studied. Materials and methods:This study was conducted on 60 postpartum women . The colostrum concentration of lactose, total proteins, triglycerides, calcium and immunoglobulin A were estimated in normal postpartum women and compared with colostrum of women having pregnancy induced hypertension and in women with anaemia during pregnancy. Results: Our study revealed significant lowering of immunoprotective factors IgA and total proteins in women with PIH and anemia. Awareness about this change in colostrum during complicated pregnancies can be a useful tool for preventive and protective paediatrics.